The Cartesian test of modern love: imagination, free will and passions - Serban, Oana (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2024)
This article tackles the role of emotions in convincing on the dualism advanced by Descartes, closely following the constitution of love at the edge of modus cognoscendi and modus volendi. The following two questions inspire the reflection on love as a spiritual exercise and a constitutive emotion for (self)knowledge: Does love represent a core-emotion for Descartes that regains his Christian thinking at the edge of his metaphysical and epistemological project, apparently excused of any religious implications? What is Descartes’s account of love and how does it (emotionally) change the sense and reception of passions? The Christian implications of love and devotion to God provide access to a so-called implicit political project engaged by Descartes’s work, grounded on the loyalty and adoration of a sovereign anointed in the name of faith.